A safety radiation marker in the cardiac catheterization lab. Issue 2 (1st April 2016) - Kostakou, Peggy M.; Damaskos, Dimitris S.; Dagre, Anna G.; Makavos, Georgios A.; Olympios, Christoforos D.
Abstract : Objective Nowadays, in order to deal with cardiovascular disease, coronary angiography (CRA) is the best tool and gold standard for diagnosis and assessment. CRA inevitably exposes both patient and operator to radiation. The purpose of this study was to calculate the radiation exposure in association with the radiation absorbed by interventional cardiologists, in order to estimate a safety radiation marker in the catheterization laboratory. Methods and results In 794 successive patients undergoing CRA and in three interventional cardiologists the following parameters were examined: radioscopy duration, radiation exposure during fluoroscopy, total radiation exposure and the number of stents per procedure. Every interventional cardiologist was exposed to 562, 936 μ Gym 2 of total radiation during CRA procedures, to 833, 371 μ Gym 2 during elective CRA + percutaneous coronary intervention (PCI) procedures and to 328, 250 μ Gym 2 during primary CRA + PCI. Hence, the total amount of radiation that every angiographer was exposed to amounted to 1, 724, 557.5 μ Gym 2 (median values). During the same period, the average radiation that every angiographer absorbed was 15, 253 while the average dose of radiation absorbed during one procedure was 0.06 mSv for each operator. Therefore, the ratio between radiation exposure and the radiation finally absorbed by every operator was 113:1 μ Gym 2 /mSv. Conclusions The present study, indicating the ratio above, offers a safety marker in order to realistically estimate the dose absorbed by interventional cardiologists, suggesting a specified number of permitted procedures and an effective level of radiation use protection tools.